Walks through historic Sandwich - Clarke, Helen (Oxbow Books, 2011)
This attractive booklet is a guide to two walks around the historic town of Sandwich, once one of the great ports of medieval England. As a Cinque port, it served successive monarchs as a military and naval base for their overseas expeditions and its trading activities extended far and wide. The town still displays signs of those prosperous centuries: an unchanged street plan, a virtually intact circuit of town walls and an exceptionally large number of well-preserved medieval houses. Two walks, clearly described with maps and copious photos, unlock the features of this fascinating town. The f.